2018
DOI: 10.1021/acsami.8b08564
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Activated SrTiO3: Photocatalytic H2 Evolution from Neutral Aqueous Methanol Solution in the Absence of Any Noble Metal Cocatalyst

Abstract: Noble metal cocatalysts are conventionally a crucial factor in oxide-semiconductor-based photocatalytic hydrogen generation. In the present work, we show that optimized high-temperature hydrogenation of commercially available strontium titanate (SrTiO) powder can be used to engineer an intrinsic cocatalytic shell around nanoparticles that can create a photocatalyst that is highly effective without the use of any additional cocatalyst for hydrogen generation from neutral aqueous methanol solutions. This intrins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 80 publications
(135 reference statements)
2
25
0
Order By: Relevance
“…have annealed commercially available SrTiO 3 and Nb‐doped SrTiO 3 single crystals at different temperatures under the H 2 atmosphere to synthesize intrinsically activated noble metal‐free photocatalysts for H 2 evolution. [ 99 ] The H 2 annealing ensued in the creation of oxygen vacancies in these materials, which were confirmed by EPR, XPS, HETEM, STEM, and elemental mapping techniques. The HRTEM and O‐mapping of SrTiO 3 annealed at 1100 °C for 4 h are depicted in Figure a,b, which displays the disordered layer at the edges of the particle.…”
Section: Vacancy Engineered Materials For Photocatalytic H2 Evolution and N2 Fixationmentioning
confidence: 81%
See 1 more Smart Citation
“…have annealed commercially available SrTiO 3 and Nb‐doped SrTiO 3 single crystals at different temperatures under the H 2 atmosphere to synthesize intrinsically activated noble metal‐free photocatalysts for H 2 evolution. [ 99 ] The H 2 annealing ensued in the creation of oxygen vacancies in these materials, which were confirmed by EPR, XPS, HETEM, STEM, and elemental mapping techniques. The HRTEM and O‐mapping of SrTiO 3 annealed at 1100 °C for 4 h are depicted in Figure a,b, which displays the disordered layer at the edges of the particle.…”
Section: Vacancy Engineered Materials For Photocatalytic H2 Evolution and N2 Fixationmentioning
confidence: 81%
“…a,d) HRTEM, elemental mapping, EELS line scan, and distribution of Ti 3+ and Ti 4+ in the selected area of SrTiO 3 annealed at 1100 °C for 4 h. Reproduced with permission. [ 99 ] Copyright 2018, ACS. e) Mechanism of H 2 evolution over SrTiO 3 /Cd0 .5 Zn 0.5 S photocatalyst.…”
Section: Vacancy Engineered Materials For Photocatalytic H2 Evolution and N2 Fixationmentioning
confidence: 99%
“…Owing to the abundance and renewability of sunlight and water, a solar-driven watersplitting process using photocatalysts is considered a long-term sustainable technology for producing hydrogen-a clean and renewable energy source. Even though various photocatalysts, such as TiO 2 , SrTiO 3 , CdS, TaON, ZrO 2 , and their assemblies, have been extensively studied, the development of novel photocatalysts that significantly enhance hydrogen production performance is still a challenging research area [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent research, a similar kind of trend was observed by Fadlallah et al for cation codoped SrTiO 3 photocatalysts for water splitting. Photocatalytic activity of SrTiO 3 codoped metal transition such as Rh, V, Sb significantly improved as compared to pristine SrTiO 3 due to the reduction of the bandgap energy of host structure 27 . Ma et al reported that the H 2 production from water splitting of transition metal-doped SrTiO 3 photocatalysts exhibited higher than that of pristine SrTiO 3 due to the presence of sub-bandgap states in the SrTiO 3 lattice under visible light 28 .…”
Section: Discussionmentioning
confidence: 97%